1970
DOI: 10.3329/bjvm.v6i1.1340
|View full text |Cite
|
Sign up to set email alerts
|

Macro-anatomy of the bones of the forelimb of Black Bengal goat (<i>Capra hircus</i>)

Abstract: In the present study, five Black Bengal goats (Capra hircus) were used to investigate the bones of fore limb during January to June 2006. It was observed topographically that the scapula was more or less similar to other ruminant animal topographically with exception that, the presence of very short coracoid process, more or less oval shaped glenoid cavity and more extensive subscapular fossa. The humerus of adult Black Bengal goat was 12.06 ± 0.27cm in length. The diameter of shaft at the level of nutrient fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 2 publications
14
24
0
1
Order By: Relevance
“…In addition to extensor and flexor muscles, tendons, ligaments, and carpal joint sacs and capsule. These findings were in agreement with those reported in textbooks (Getty, 1975;Nickel et al, 1986;Siddiqui et al, 2008;Hussain, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to extensor and flexor muscles, tendons, ligaments, and carpal joint sacs and capsule. These findings were in agreement with those reported in textbooks (Getty, 1975;Nickel et al, 1986;Siddiqui et al, 2008;Hussain, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Two thoracic limbs were obtained from Zagazig abattoir, then after, the bones of carpal region were prepared by boiling method (Siddiqui et al, 2008). Before boiling, the bones were wrapped separately with a net to prevent the loss of small bones.…”
Section: Bone Preparationsmentioning
confidence: 99%
“…The deeper musculospiral groove is present in the lateral portion of the shaft. This was in agreement with the reports of Siddiqui et al (2008) in Black Bengal goat.…”
Section: Scapulasupporting
confidence: 83%
“…The carpals of the proximal row from medial to lateral were: radial carpal or scaphoid (ossa carpi radiale vel scaphoideum), intermediate carpal or semilunar (ossa carpi intermedium vel os lunatum), ulnar carpal or cuneiform (ossa carpi ulnare vel os triquetrum) and accessory carpal or pisiform (ossa carpi accessorium vel os pissiforme). The bones of the distal row were composed of second and third fused carpal or os magnum (ossa carpale II et III vel os trapazoideocapitatum) and fourth carpal or unciform (os carpale IV vel os hamatum) as reported by Konig and Liebich (2006), Akers and Denbow (2008) and Frandson et al (2009) in ruminants, Raghavan (1964) in ox, Getty (1975 in sheep, in Black Bengal goat Siddiqui et al (2008), in chital Choudhary et al (2013) and Choudhary et al (2015) in blackbuck. These findings were not similar with the reports of Konig and Liebich (2006) in pig, where a typical pattern of eight carpal bones composed in two rows of four carpals each was found also in dog (Miller et al 1964) Getty (1975), Konig and Liebich (2006) and Akers and Denbow (2008) in horse were reported that proximal row composed of radial, intermediate, ulnar and accessory while distal row was composed of first, second, third and fourth but as per Smuts and Bezuidenhout (1987) in dromedary the first carpal was not present in proximal row while in distal row first carpal was absent from the typical pattern.…”
Section: Resultsmentioning
confidence: 62%
“…1, 2 & 7) bone was situated medially and was larger than fourth carpal as reported by Raghavan (1964) in ox, Choudhary et al (2013) in chital and Choudhary et al (2015) in black buck. The first carpal bone was absent as reported in ox (Raghavan, 1964), in dromedary (Smuts and Bezuidenhout, 1987) and in Black Bengal goat (Siddiqui et al, 2008); however it was observed by (Miller et al, 1964) in dog, (Getty, 1975 andAkers andDenbow, 2008) in horse, (Ozkan, 2004) in hedgehogs and (Konig and Liebich, 2006) in man and pig.…”
Section: Resultsmentioning
confidence: 77%